IMPLEMENTASI APLIKASI SISTEM INFORMASI INVENTORY DATA BARANG EKSPOR PADA PT. HARVEST GLOBAL NIAGA: IMPLEMENTASI APLIKASI SISTEM INFORMASI INVENTORY DATA BARANG EKSPOR PADA PT. HARVEST GLOBAL NIAGA - Nanang Nuryadi; Bakhtiar Rifai; Reza Bagaskoro (Institute of Computer Science (IOCS), 2019)
In the current information system condition PT. Harvest Global Niaga is less than a maximum in searching and inputting data on exported goods. Difficulty finding data items because the existing data processing system is still in the form of data files and some data stored in Excel format. Therefore, technology assistance is needed in supporting all these activities. In the process, of course, it must run effectively and efficiently as possible so that employees can easily find the information available, the method used should be more systematic, especially in processing data on exported goods, in the hope of facilitating the process than using a computerized system. So, the author designed the application to facilitate employees at PT. Harvest Global Niaga. The inventory information system is a data processing application that is very efficient and effective to help work.